Efficacy and safety of various drugs used for the treatment of nonneurogenic lower urinary tract symptoms in tertiary care hospital - Dwivedi, Shikha; Dhasmana, Dilip Chander; Biswas, Manoj; Dixit, Vimal Kumar; Agrawal, Neeraj Kumar (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) are common in elder men. Previously surgical treatment was mainstay of treatment of BPH. But now number of drugs alone or combined are clinically used for this disorder. Primary aim was to study the prescribing pattern of different drug therapies and their role in treating LUTS/BPH by evaluating their efficacy and safety in tertiary health care centre. Methods: An observational study including 78 male patients ≥45 years, newly diagnosed with LUTS from April 2014 to May 2015. Patients were followed up every 4 weeks for 3 months after the drug has been prescribed. Efficacy assessment was done on basis of change in IPSS score over 12 weeks. Data was expressed in percentage and Mean ±SD. Results: Mean age of Patients was 64.94 years. Alpha blockers are mainstay prescribed drug either as monotherapy (48.7%) or with 5 alpha reductase inhibitor-dutasteride (38.4%) and with antimuscarinic –Tolterodene (12.8%). Among alpha blockers Tamsulosin (58.97%) was most commonly prescribed, followed by Silodosin (20.5%) and Alfuzosin (20.5%). All drug treatment results in significant improvement with dizziness being the most common adverse event. A subgroup analysis in symptoms was done comparing alpha blockers. All alpha blockers have near about similar efficacy with no significant difference. Conclusions: Alpha blockers are main drugs prescribed in management of LUTS/BPH with near about similar efficacy of all alpha blockers.